2021
DOI: 10.1038/s41391-020-00309-w
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor gain in circulating free DNA and splicing variant 7 in exosomes predict clinical outcome in CRPC patients treated with abiraterone and enzalutamide

Abstract: Background Androgen receptor (AR) signaling inhibitors represent the standard treatment in metastatic castration resistance prostate cancer (mCRPC) patients. However, some patients display a primary resistance, and several studies investigated the role of the AR as a predictive biomarker of response to treatment. This study is aimed to evaluate the role of AR in liquid biopsy to predict clinical outcome to AR signaling inhibitors in mCRPC patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 37 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…TMPRSS2:ERG is the predominant gene fusion in PCa where TMPRSS2 protein functions with overexpressed ERG; an ETS transcription factor thereby contributing to androgenresistance in PCa [62][63][64]. A recent study showed that AR variant, AR-V7 RNA is present in exosomes in patients treated with AR pathway inhibitors Enzalutamide and Abiraterone as a primary therapy and is predictive of resistance to AR signaling inhibitors [65].…”
Section: Exosome-contained Micrornas Messenger Rnas and Long Non-comentioning
confidence: 99%
“…TMPRSS2:ERG is the predominant gene fusion in PCa where TMPRSS2 protein functions with overexpressed ERG; an ETS transcription factor thereby contributing to androgenresistance in PCa [62][63][64]. A recent study showed that AR variant, AR-V7 RNA is present in exosomes in patients treated with AR pathway inhibitors Enzalutamide and Abiraterone as a primary therapy and is predictive of resistance to AR signaling inhibitors [65].…”
Section: Exosome-contained Micrornas Messenger Rnas and Long Non-comentioning
confidence: 99%
“…[41] Exosomal AR-V7 is associated with resistance to ABI and ENZ. [44,56] AR-V7 in biopsies detected by RISH is associated with a shorter PFS.…”
Section: Ar-v7mentioning
confidence: 92%
“…Isolated CTCs can be further analyzed by single-cell sequencing methods for more detailed DNA or RNA profiling [45,46]. AR-V7, detected from plasma-derived exosomal RNA, similarly predicts resistance to abiraterone and enzalutamide [44,56]. Such combinatorial liquid biomarkers are yet to be tested in a prospective fashion.…”
Section: Ar-v7mentioning
confidence: 99%
“…Moreover, EVs which transport lncRNA SNHG14 or TGF-β1 could be used for the same function; in fact, both populations of EVs are present in non-responding patients [153,154]. In prostate cancer, the presence of Arv7 mRNA in circulating EVs predicts resistance to hormone therapy and correlates with a short OS [155].…”
Section: Evs Use As Liquid Biopsymentioning
confidence: 99%